Subjetividade e tele-existência na era da comunicação virtual: o hiperespetáculo da dissolução do sujeito nas redes sociais de relacionamento - Bello, Cíntia Dal (2013)
The objective of this research is to understand the phenomenon of cybermediatic tele-existence existence in real time enabled by cybercultural communication and relationship platforms in fixed or mobile devices to gauge their socio-anthropological impact and, based on an analysis of the relationship between subjectivity, tele-existence and cybercultural visibility, examine the individual‟s status in the hyper-spectacular dimension. The object of study is the spectral, signic corporality, the signic-imagerial arrangement, which gives the user an apparent organicity that renders him present in communication environments. The delimitation of the corpus involves the observation of profiles, avatars and other interfaces of subjective projection in social networks, metaverses and social games to understand the imperative process of continuous spectralization of existence resulting from the natural desire for self-exposure. Having stated the above, the main question guiding this research is: If the projection of existence in cyberspace is aimed at providing a thumbnail sketch of the individual in the midst of information flows, giving him cybermediatic visibility, why is its effect usually that of contributing to his dissolution or invisibility? To answer this question, we propose the hypothesis that to tele-exist, albeit perceived as a pleasant pastime, constitutes an agonistic dispute for the mediatic center stage, which leads to the excessive production of information as a strategy to keep the user continually in the limelight. Everyone wants to appear because they fear insignificance, which is associated with the fear of nonexistence. Because existence from now on seems to make sense only when it passes through cybermediatic hyper-spectacularization, the essence of the individual‟s composition in cyberspace has shifted from Who I am to What I‟m thinking/doing. The effect of the information saturation and excessive visibility resulting from this shift is that every act of projection simultaneously becomes one of dissolution (in)visibility. The methodology for this research consisted of a literature survey and a qualitative field study, based on netnography (translated into its main elements: noninvasive entry into the aforementioned platforms, exploratory survey of profiles and avatars, participant observation, and unstructured interviews with users). The theoretical foundation of this interdisciplinary research (philosophical, sociological, anthropological and psychoanalytical), which provided the necessary epistemological frameworks for the analysis of the object of study, for checking hypotheses, and for solving the research problem, includes philosophical postmodernism, French post-structuralism, cultural semiotics and phenomenological sociodromology